KORELASI DISIPLIN BELAJAR DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VI SD 1 MIJEN - Sa'adah, Karima Noor Malikatus; Kironoratri, Lintang; Ermawati, Diana (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
TThis research is a quantitative correlational method research conducted in class VI of SD 1 Mijen with 36 students as research subjects. The independent variable in the study is learning discipline while the dependent variable is the students' Indonesian language learning outcomes. In collecting data, the researcher used research instruments in the form of questionnaires and documentation. Data analysis was carried out using descriptive statistical analysis and hypothesis testing using product moment correlation. The results of the study classified learning discipline into 2 categories, namely in the very good category of 70%, and the good category of 30%. The results of the product moment correlation coefficient calculation produced an r-count value of 0.985 and a significance of 0.000 <0.05. Based on the guidelines for interpreting the correlation coefficient, the value of 0.985 is in the range of 0.80 - 1,000, which is included in the category of a very strong relationship. Based on the results of the research that has been conducted at SD 1 Mijen, it can be concluded that students who achieved learning discipline in the very good category were 25 students, and in the good category there were 11 students. The results of the study also showed that there was a positive and significant relationship between learning discipline and students' Indonesian language learning outcomes. The suggestion in this study is that teachers should pay attention to factors that influence student learning outcomes, such as student learning discipline so that students in following the learning process have enthusiasm or passion in learning and students can use their time well and usefully, not only for playing.